2004
DOI: 10.1080/14622200412331320770
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions about cigarette smoking and risks among college students

Abstract: The objective of the present study was to describe how college students perceive the risks of cigarette smoking and addiction to nicotine. Data came from a self-administered survey of 1,020 college students enrolled in two 4-year liberal arts colleges in the United States. The survey was conducted in the fall of 2001. Smokers and nonsmokers differed markedly in their perceptions about the health risks associated with short-term exposure to smoking. College students in this sample who smoked did not fully compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 14 publications
1
41
2
Order By: Relevance
“…Contrary to other studies, there was no significant difference in knowledge scores between current smokers and current non-smokers [7,18,27,28]. A prior study among university students in Jordan, with 28.6% of their sample being current smokers, found that non-smokers were more aware of the harmful effects of smoking [7].…”
Section: Discussioncontrasting
confidence: 43%
“…Contrary to other studies, there was no significant difference in knowledge scores between current smokers and current non-smokers [7,18,27,28]. A prior study among university students in Jordan, with 28.6% of their sample being current smokers, found that non-smokers were more aware of the harmful effects of smoking [7].…”
Section: Discussioncontrasting
confidence: 43%
“…The challenge to clinicians who treat college students and other young adults is that LITS are more resistant to antismoking efforts as many do not consider themselves smokers Levinson et al, 2007;Moran, Wechsler, & Rigotti, 2004) and believe that they will not become addicted, will be able to quit on their own when they want to, and don't smoke enough to present a risk to their health (Morley, Hall, Hausdorf, & Owen, 2006;Murphy-Hoefer, Alder, & Higbee, 2004;. Contrary to these beliefs, there is growing evidence that even occasional smokers experience greater health risks when compared with nonsmokers Bjerregaard et al, 2006;Husten, 2009;Okuyemi et al, 2002), and they are less successful at quitting when they try (Everett et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Younger cohorts of women have also been exposed to public health information about the risks associated with smoking. There is evidence from both community and college samples that smokers have a general awareness of the long-term health risks associated with tobacco use, such as cancer (Bansal et al, 2004;Murphy-Hoefer, Alder, & Higbee, 2004). However smoking may also be perceived as a way to gain some benefits in the short-term.…”
Section: Smoking and Self-objectificationmentioning
confidence: 95%